Comparison of stochastic estimation methods with conditional events optimization for the reconstruction of the flow around a supercritical airfoil in transonic conditions. (10th September 2016) - Arnault, A.; Dandois, J.; Foucaut, J.-M.
Highlights: Stochastic estimation methods are applied to estimate flow fields of an airfoil. Multi-time-delay linear stochastic estimation holds the most accurate estimation. High frequency, short scale information is not accurately estimated. A sensor location optimization algorithm is proposed to choose time delays. Stochastic estimation is shown to filter Gaussian noise in the flow field. Abstract: Unsteady Reynolds Average Navier–Stokes simulation and Zonal Detached Eddy Simulation of an OAT15A airfoil in transonic buffet conditions are used to investigate the abilities of several stochastic estimation methods to reconstruct and predict turbulent flow. In particular the comparison between the two simulations estimations allows us to identify limitations of these methods in relation to some characteristics of turbulent flow. A sensor location optimization algorithm is proposed and tested, as well as its extension to the choice of delays for the multi-time-delay stochastic estimation. The impact of Gaussian noise is also assessed.